BLOOD VESSELS DEVELOPMENT IN THE WOUND HEALING PHASE OF THE WISTAR RAT INCISION DUE TO ANTIBIOTICS DROP - Amalia, Nabilah Rizky; Jayawardhita, Anak Agung Gde; Samsuri, Samsuri (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p12, 2022)
The mechanism of administration of antibiotic drops on incision wound healing in terms of the number of blood vessels is not yet known for its effectiveness. Therefore, this study aims to determine the efficacy of administering antibiotic drops on the number of blood vessels in the incision wound of Wistar rats ( Rattus norvegicus ). This study used 24 female Wistar rats with a body weight of about 150-200 grams each. Following the adaptation process in one week, an incision wound at 1.5 cm in a depth of up to the muscle (0.5 mm) is made in four groups with the control division (T 0 ) given physiological NaCl. Treatment I (T 1 ) drops of oxytetracycline antibiotics, treatment II (T 2 ) drops of antibiotic amoxicillin, and treatment III (T 3 ) drops of antibiotic cefotaxime. In each group of rats, three drops of antibiotic are given or 0.15 ml. After being treated, the skin samples of the incised mice were taken for histopathological examination to observe the number of blood vessels. The data results on the mean difference in the number of blood vessels were analyzed using Analysis of Variant (ANOVA). It continued with Duncan's Post Hoc test if there were significant differences. The results of the comparison of the mean number of blood vessels in the four treatments were 88.17 ± 77.78, 370.33 ± 277.14, 213.33 ± 41.44, and 268.17 ± 141.10. The results showed that antibiotics from the tetracycline group had the highest mean number of blood vessels compared to the other three treatments.